Microbial metabolic engineering for the production of isoprenoids in escherichia coli - Ji, Lin (2013)
Isoprenoids, consisting of more than 50,000 compounds, have many functions in plants, animals, and microorganisms. Many isoprenoids are used for the treatment of human diseases, such as malaria and cancers. Microbial metabolic engineering has been developed recently as a new approach to increase the production of isoprenoids. This method is easier and less expensive than chemical synthesis, and produces more isoprenoids than plant extraction method. All isoprenoids are synthesized from IPP and DMAPP through the mevalonate pathway or nonmevalonate pathway. This review focuses on the metabolic engineering of these two isoprenoid synthesis pathways for the production of functional isoprenoids in Escherichia coli. Despite some successes, the quantity of isoprenoids currently produced still cannot meet the demands. Thus, more efforts in developing new methods for further improving isoprenoid production are required.